Stabilization of Expansive Soil Using Marble Powder and Phosphoric Acid against Physical Properties and SEM-EDS Tests - Ambrosio Martins Nuno; Syahril Syahril (Widyagama University of Malang, 2023)
The Gedebage region faces a myriad of challenges, including road deformations, swelling of roads and bridges, and cracks in drainage foundations, buildings, and asphalt concrete. To address these issues, a comprehensive analysis of soil physical properties was conducted at the POLBAN soil mechanics laboratory, along with chemical tests at the POLMAN laboratory. The primary objective was to understand the physical properties and mineral composition of Gedebage soil and develop effective soil management strategies. Soil stabilization was employed as a method to enhance infrastructure resilience in Gedebage. Marble powder waste (MPW) was utilized in varying concentrations (2.5%, 4%, 5.5%, and 7%) along with 4% phosphoric acid (PA) to optimize the solution. MPW filled soil pores and improved cohesion, while PA reduced moisture content, enhanced particle bonding, increased load-bearing capacity, and minimized soil volume changes. Initial soil tests revealed a high plasticity index (PI) of 54.20%, indicating Gedebage, expansive clay soil nature with significant potential for expansion and plasticity. The AASHTO classified it as